The application of FGD to support concept of National Policy on health and safety work procedures on ATC employees in Indonesia - Lalu Muhammad Saleh; Syamsiar S. Russeng; Istiana Tadjuddin; Nurul Mawaddah Syafitri; Iva Hardi Yanti; Mahfuddin Yusbud (Elsevier, 2021)
Objective: This study aims to conduct a focused discussion regarding the concept of a national policy on health and safety work procedures for ATC employees in Indonesia. Methods: The research is a qualitative study with case study design. Data was collected through Focus Group Discussion (FGD) method. A total of 11 informants participated in this study. Data were analyzed with content analysis method. Results: It was found that all informants have positive perception to this model and agree to support the ATC employee's policy development. Conclusion: It can be concluded that in general, all informants support the concept of a national policy on health and safety work procedures for ATC employees in Indonesia. Therefore, it is hoped that a policy will be formed that focuses on improving ATC performance so that it can work healthy and safely.